2013
DOI: 10.1007/s12013-013-9574-z
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-methyltransferase in Non-small Cell Lung Cancer: Promising Results for Targeted Anti-cancer Therapy

Abstract: Lung cancer, predominantly non-small cell lung cancer (NSCLC), is currently the most common cause of malignancy-related death in the world. Despite advances in both detection and treatment, its incidence rate is still increasing. Therefore, effective strategies for early detection as well as molecular therapeutic targets are urgently needed. We focused on the enzyme nicotinamide N-methyltransferase (NNMT). NNMT expression levels were investigated in tumor, tumor-adjacent, and surrounding tissue samples of 25 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…An enhanced expression of NNMT has been reported in a number of cancers, such as glioblastoma [47], stomach adenocarcinoma [48,49], papillary thyroid cancers [50,51], renal [52,53], and oral squamous cell carcinomas [54][55][56], colorectal cancer [57], bladder [58], lung and pancreatic cancers [59][60][61]. In our previous works, we explored NNMT expression in renal cell carcinoma (ccRCC) [52], oral squamous cell carcinoma (OSCC) [54][55][56], urothelial carcinoma (UC) of the bladder [58] and non-small cell lung cancer (NSCLC) [60]. Although several cancers have been associated with abnormal NNMT expression, its role in cancer cell metabolism remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An enhanced expression of NNMT has been reported in a number of cancers, such as glioblastoma [47], stomach adenocarcinoma [48,49], papillary thyroid cancers [50,51], renal [52,53], and oral squamous cell carcinomas [54][55][56], colorectal cancer [57], bladder [58], lung and pancreatic cancers [59][60][61]. In our previous works, we explored NNMT expression in renal cell carcinoma (ccRCC) [52], oral squamous cell carcinoma (OSCC) [54][55][56], urothelial carcinoma (UC) of the bladder [58] and non-small cell lung cancer (NSCLC) [60]. Although several cancers have been associated with abnormal NNMT expression, its role in cancer cell metabolism remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As a phase II metabolizing enzyme, NNMT is involved in the biotransformation of many drugs and xenobiotic compounds [6,7,21]. Abnormal NNMT expression has been reported in many human neoplasms including brain, nasopharynx, oral cavity, thyroid, lung, liver, stomach, kidney, bladder and colon [8,9,10,11,12,13,14,15,16,17,18]. Furthermore, a recent study showed that NNMT overexpression was associated with increased radioresistance via regulating nicotinamide metabolism [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is predominantly expressed in liver and weakly expressed in other tissues like kidney, lung, skeletal muscle, placenta, heart and brain [6]. Abnormal expression of NNMT has been found in numerous cancers, including glioblastoma [8], hepatocellular carcinoma [9], thyroid carcinoma [10], gastric cancer [11], renal cell carcinoma [12], colorectal cancer [13], oral squamous cell carcinoma [14], bladder cancer [15], non-small cell lung cancer [16], and nasopharyngeal carcinoma [17]. These results suggest that NNMT may serve as a potential biomarker for tumor diagnosis and a new therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…The top expressed gene other than SOCS3 under both treatment paradigms was PLA2G2A [type-II secretory phospholipase A2: sPLA 2 (AII)], an enzyme associated with acute respiratory distress syndrome (ARDS) (35,61,74). PLA2G2A expression was higher under IL-6 trans-signaling conditions compared with classical IL-6 conditions ( (58,59), IL13RA1 (interleukin 13 receptor alpha 1) (5), and SOD2 (superoxide dismutase 2) (41). OSMR (oncostatin M receptor), a member of the IL-6 receptor family (complexes with coreceptor gp130) (15), was significantly elevated under both treatment conditions.…”
Section: Kinetics Of Activation and Functional Effects Of Classical Il-6mentioning
confidence: 99%